A novel denitrifying phosphorus removal and partial nitriﬁcation, anammox (DPR-PNA) process for advanced nutrients removal from high-strength wastewater. (February 2021) - Zhang, Xingxing; Wang, Chaochao; Wu, Peng; Xia, Yunkang; Chen, Ya; Liu, Wenru; Xu, Lezhong; Faustin, Fangnigbe
Abstract: This study developed a novel DPR-PNA (denitrifying phosphorus removal, partial nitrification and anammox) process for sustaining high-strength wastewater treatment in a modified continuous flow reactor without external carbon source. After 259-days operation, a synchronous highly-efficient total inorganic nitrogen, PO4 3- -P and CODcr removal efficiencies of 88.5%, 89.5% and 90.1% were obtained, respectively even influent nitrogen loading rate up to 3.2 kg m −3 d −1 . Batch tests revealed that denitrifying phosphorus accumulating organisms (DPAOs) using NO3 − -N as electron acceptors significantly enriched (74% in total PAOs), which emerged remarkable positive impacts on deep-level nutrient removal as the key limiting factor. Furthermore, the NO2 − -N inhibitory threshold value (∼20.0 mg L −1 ) for DPAOs was identified, which demonstrated as an inhibitory component in excessive recycling NOx − -N. From the molecular biology perspective, Dechloromonas -DPAOs group (18.59%) dominated the excellent dephosphatation performance, while Nitrosomonas -AOB (ammonia oxidizing bacteria) group (16.26%) and Candidatus_Brocadia -AnAOB (anammox bacteria) group (15.12%) were responsible for the desirable nitrogen loss process. Overall, the present work highlighted the novel DPR-PNA process for nutrients removal is a promising alternation for wastewater of high nitrogen but low carbon. Graphical abstract: Image 1 Highlights: DPR-PNA-ABR process could sustain robust high-strength NH4 + -N wastewater treatment. Regulating NOx − -N recirculation to relieve NO2 − -N inhibition on DPAOs made senses. DPAOs were significantly enriched with elevated nitrogen loading in DPR process. Candidatus_Brocadia (15.12%) played dominant roles in DPR-PNA nitrogen removal. Functional non-interfering groups cooperated stably for advanced nutrients removal.